Reinterpretation of Classic Proton Charge Form Factor Measurements - Mihovilovič, Miha; Higinbotham, Douglas W.; Bevc, Melisa; Širca, Simon (Frontiers in Physics, 2020)
In 1963, a proton radius of 0.805(11) fm was extracted from electron scattering data and this classic value has been used in the standard dipole parameterization of the form factor. In trying to reproduce this classic result, we discovered that there was a sign error in the original analysis and that the authors should have found a value of 0.851(19) fm. We additionally made use of modern computing power to find a robust function for extracting the radius using this 1963 data's spacing and uncertainty. This optimal function, the Pade (0,1) approximant, also gives a result which is consistent with the modern high precision proton radius extractions.